2020
DOI: 10.24843/jiab.2020.v15.i01.p07
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance, Market Share, and Intellectual Capital Disclosure: Evidence from the Indonesian Agriculture and Mining Sectors

Abstract: Using a sample of Indonesian agricultural and mining companies, this study aims to provide empirical evidence to prove the effects of auditor type, the board size, and audit committee on intellectual capital disclosure (ICD). The sample consisted of 18 agricultural and 28 mining companies, which were chosen using the content analysis method. The five-year observation period lasted from 2013 to 2017, resulting in 230 units of analysis. Data analysis employed a panel regression model with panel data testing. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Customer capital, a part of the IC model, involves external relationships, including those with consumers, suppliers, and R&D. Thus, the management of intangible assets to the extent that it increases value for the company, achieving competitive advantage and enhancing productivity, is the essence of IC (Ulum, 2020). The synergy of human resources, innovation, and technology is integral to creating IC (Hatane et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Customer capital, a part of the IC model, involves external relationships, including those with consumers, suppliers, and R&D. Thus, the management of intangible assets to the extent that it increases value for the company, achieving competitive advantage and enhancing productivity, is the essence of IC (Ulum, 2020). The synergy of human resources, innovation, and technology is integral to creating IC (Hatane et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There are dissimilarities in the results of an investigation that examines the audit committee on intellectual capital disclosures produced by Li, Mangena and Pike (2012), Haji, A.A. (2015), Hatane, Kuanda, Cornelius ,and Tarigan (2020), Taliyang andJusop (2011), andIsnalita (2018). Li et al (2012), and Balasundaram, (2018) which revealed that the audit committee has a positive impact on the disclosure intellectual capital.…”
Section: Introductionmentioning
confidence: 99%